Wykorzystanie modeli dyskryminacyjnych do oceny kondycji finansowej Zakładów Tłuszczowych Kruszwica S.A. - Wasilewski, Mirosław; Domańska, Teresa (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2012)
The following study determines the risk prediction of bankruptcy of ZT “Kruszwica” industrial enterprise, using certain discriminatory models in terms of maintaining financial liquidity. The research, covering the period from 2008 to 2010, was based on a unit, quarterly financial statements. It was observed that liquidity ratings reached a satisfactory level. However, two of the accepted models showed a difficult financial situation of ZT “Kruszwica” S.A. For instance, E.I. Altman’s model indicated threat of bankruptcy in 2008. Contrary to A. Mączynska’s model, which informed about a bad financial condition in the second quarter of 2010. The other models proved that the company was developing dynamically at that time. To conclude, the prediction models of bankruptcy can have ambiguous results. However, discriminatory models can be treated as part of the financial situation of a company and fundamental analysis.